Transitional structure of 332〈113〉β twin boundary in a deformed metastable β-type Ti-Nb-based alloy, revealed by atomic resolution electron microscopy. (June 2018) - Chen, Bin; Sun, Wei
Abstract: In this work, the boundary structure of the 332〈113〉β deformation twin in a deformed metastable β-type Ti-Nb-Pd alloy has been clearly revealed by means of high-angle annular dark-field scanning transmission electron microscopy at atomic-resolution level. It is found that stress-induced α″ martensite structure remains in the 332β twin boundary region, exhibiting a gradual transition to the β structure with an orientation relationship of (1 3 ¯ 0)α″ //(332)β . This finding provides a direct experimental evidence to verify that the formation of a 332β twin in deformed metastable β-type Ti-Nb-based alloys can be associated with a reversible β-to-α″ martensitic transformation. Graphical abstract: Unlabelled Image